2021
DOI: 10.1002/adfm.202106996
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Electrochemical Behaviors of the Electrode‐Electrolyte Coupling toward Advanced Electrochemical Energy Storage Device

Abstract: Aqueous electrochemical energy storage devices (AEESDs) exhibit tremendous potential for grid‐scale energy storage due to their high ionic conductivity, high safety, and environmental friendliness. Nevertheless, the improvement of energy density is always accompanied by the loss of power density due to the sluggish ion migration in the bulk of the electrode. Redox electrolytes are proposed as one of the most promising strategies to expand from electrode materials to the whole device to improve the energy densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…It is important to note that when each voltage step is long enough, the more favorable it is for probing the true reaction occurring at the electrodes. [156] For a conventional redox system, the i i obtained is large. As time progresses, the current decreases as the Reproduced with permission.…”
Section: Multipotential Steps Measurement (Mpsm)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that when each voltage step is long enough, the more favorable it is for probing the true reaction occurring at the electrodes. [156] For a conventional redox system, the i i obtained is large. As time progresses, the current decreases as the Reproduced with permission.…”
Section: Multipotential Steps Measurement (Mpsm)mentioning
confidence: 99%
“…b) Schematic for MPSM (red curve: input potential, black curve: output current),and c) MPSM curves with different potential steps. Reproduced with permission [156]. Copyright 2021, Wiley-VCH GmbH.…”
mentioning
confidence: 99%
“…5,6 Unfortunately, despite significant improvements in battery performance, ESDs have significant security flaws that limit their further application. [7][8][9] Super-fast charging or discharging and thermal abuse conditions such as short-circuiting and overcharging pose the risk of thermal runaway, which can have severe consequences. 10,11 For example, on October 15, 2022, South Korea's key data center lost power due to the combustion of LIBs, interrupting the services of the country's two Internet giants, Naver and Kakao.…”
Section: Introductionmentioning
confidence: 99%
“…26 Sun et al performed studies on the electrochemical behavior between the electrode materials and electrolyte ions, and they found that a wrinkled electrode surface greatly benefits the adsorption of ions and the formation of electronic double layers, in which the excessive ions on the surface ensure effective electrode-material-related redox reactions, subsequently leading to an improvement in the capacity performance, where the confined electrolyte ions in the wrinkled regime reduce the self-charging effect caused by the ion drift. 27…”
Section: Introductionmentioning
confidence: 99%
“…26 Sun et al performed studies on the electrochemical behavior between the electrode materials and electrolyte ions, and they found that a wrinkled electrode surface greatly benefits the adsorption of ions and the formation of electronic double layers, in which the excessive ions on the surface ensure effective electrode-material-related redox reactions, subsequently leading to an improvement in the capacity performance, where the confined electrolyte ions in the wrinkled regime reduce the self-charging effect caused by the ion drift. 27 Here, we take the view that the transition-metal oxide electrode materials require an integral form with a welldefined local structure for effective electrochemical reactions during electrochemical charge/discharge processes, using the prototype of nickel oxide as the cathode of a supercapacitor device. In the experiments, we have developed the dynamic thermal oxidation route (i.e., electrical annealing) to fabricate three-dimensional (3D) nano-folded NiO, in which Ni was oxidized into NiO in an extremely rapid manner in air leading to the formation of the nano-folded structure in the products due to the uniaxial and biaxial shrinkage of the surface NiO.…”
Section: Introductionmentioning
confidence: 99%